Cardiovascular family history increases the risk of disease recurrence after a first myocardial infarction. (25th November 2020) - Wahrenberg, A; Magnusson, P; Kuja-Halkola, R; Habel, H; Hambraeus, K; Jernberg, T; Svensson, P
Abstract: Background: Despite recent advances in secondary prevention, recurrent cardiovascular events are common after a myocardial infarction (MI). It has been reported that genetic risk scores may predict the risk of recurrent cardiovascular events. Although patient-derived family history is a composite of both genetic and environmental heritability of atherosclerotic cardiovascular disease (ASCVD), it is an easily accessible information compared to genetically based risk models but the association with recurrent events is unknown. Purpose: To evaluate whether a register-verified family history of ASCVD is associated with recurrent cardiovascular events (rASCVD) in patients after a first-time MI. Methods: We included patients with a first-time MI during 2005 – 2014, registered in the SWEDEHEART SEPHIA registry and without prior ASCVD. Follow-up was available until Dec 31st, 2018. Data on relatives, diagnoses and prescriptions were extracted from national registers. A family history of ASCVD was defined as a register-verified hospitalisation due to MI, angina with coronary revascularization procedures, stroke or cardiovascular death in any parent. Early history was defined as such an event before the age of 55 years in fathers and 65 years in mothers. The association between family history and a composite outcome including recurrent MI, angina requiring acute revascularization, ischaemic stroke and cardiovascular death during follow-up was studied with Cox proportional hazard regression with time from SEPHIA registry completion as underlying time-scale, adjusted for age with splines, gender and year of SEPHIA registry. Regression models were then further adjusted for hypertension, diabetes, smoking and for a subset of patients, LDL-cholesterol (LDL_C) at time of first event. Results: Of 25, 615 patients, 2.5% and 32.1% had an early and ever-occurring family history of ASCVD, respectively. Patients with early family history were significantly younger than other patients and were more likely to be current smokers and have a higher LDL-C (Median (IQR) 3.5 (1.1) vs 3.3 (1.1) mmol/L). In total, 3, 971 (15.5%) patients experienced the outcome. Early family history of ASCVD was significantly associated with rASCVD (Hazard ratio (HR) 1.52, 95% confidence interval (CI) 1.23–1.87), and the effect was sustained when adjusted for cardiovascular risk factors (HR 1.48, 95% CI 1.20–1.83) and LDL-C (HR 1.35, 95% CI 1.04–1.74). Ever-occurring family history was weakly associated with ASCVD (HR 1.09, 95% CI 1.02 – 1.17) and the association remained unchanged with adjustments for risk factors. Conclusions: Early family history of cardiovascular disease is a potent risk factor for recurrent cardiovascular events in a secondary prevention setting, independent of traditional risk factors including LDL-C. This is a novel finding and these patients may potentially benefit from intensified secondary preventive measures after a first-time MI. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): This work was funded by grants from The Swedish Heart and Lung Association